(untitled) - ALLAMANDA AGUSTYA OKSAW, DENNIS (Language Horizon: Journal of Language Studies, 2014)
BELLA’S ANXIETY IN STEPHANIE MEYER NEW MOON DENNIS ALLAMANDA AGUSTYA OKSAWA S1 SASTRA INGGRIS FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI SURABAYA (allamanda_03@yahoo.com) Abstract This study is aimed to present anxiety as the experienced by Bella as the main character of Stephanie Meyer’s novel entitled New Moon. Anxiety is an unpleasant emotion which is characterized once in at times in varying degrees. Anxiety is also the main concept of a human when they are in danger situation or face a problem in her life. The purposes of this study are: (1) To depict the anxiety in Isabella “Bella” Swan in Stephanie Meyer’s New Moon (2) To find out the responses of Isabella “Bella” Swan in Stephanie Meyer’s New Moon. In order to get a good analysis, it uses theory anxiety in human life and theories of self defense mechanism are used as tools to support the process in analyzing the anxiety of Isabella “Bella” Swan. The result of this study shows that: (1) Bella is getting the neurotic anxiety. She always thinks about her dream when Edward never changes her to be a vampire, so she cannot live with Edward forever. The differences make her always feels anxious and she starts depress when Edward leaves her alone because of the accident in Edward’s house (2) Bella conducts the responses of her anxieties. She forgets her anxiety for a while because Jacob Black is known as a wolf who always keeps her in every dangerous situation, when a vampire is attacked her. Bella feels comfort when Jacob is beside her. Key terms: anxiety, defense-mechanism INTRODUCTION Literature is the reflection of human life. It has a high position in human civilization, for it has been used by human being as an apparatus to express thought, critics, and social phenomena in chronological way as told by graham little ( 1996:1 ) “ literature may fairly be regarded as the chief art of mankind”. Therefore literature can also be considered as a social control to find the same perception on evaluating a moral distortion in human life. In getting better understanding the human life and problem, a literary work is a complete thought, because it conveys moral education, hatred, love, happiness, or obsession. There are some kinds of literary works they are short story, poem, drama and novel which can be analyzed for studying. Some kinds of literary works above discuss the process of human life such as thinking the solution and solving the problem. Both of them are the key term to make an easiest life if the problem comes to human life and people should overcome it as well as possible. It is the same as the statement “life is not easy”, it is the word that said by Sigmund Freud. People may not escape from the problem but it should be provided and overcome. Necessity is the important thing that should be fulfilled by human. There are a lot of cases will appear when we want to overcome the necessities in our life, it is called problem. Problem always appear in the form of the obstacles in getting what people need and what people want. It is natural that happen in our daily life. A problem certainly has a solution. It is the term that people often hear. As a human someone may not escape from his or her problem but it should be overcome with his or her way. People should never be afraid to deal with it. If someone afraid faces the problem, it is caused anxiety so that she or he always thinks it. For a long period of time, anxiety is a psychological problem which can be caused by several factors, such as nightmares, fear, sadness, or happiness. Sometimes, people who are anxious do not realize they feel. In literary works, the author sometimes shows anxiety of the character in different situation. The author creates a conflict that makes the character on the novel seem anxious, frustrated, guilty, and afraid. Besides, the author shows what is going to happen in solving his or her problem that makes the reader wants to know the story. In addition, this study reveals one of literary works which also has connection between social issues and the human personalities in society. This study is an interested to be learnt because people can recognize someone’s feeling or thought and understand the symptom which is happen in studying psychology so that people are not afraid or confused when they face problem. Psychology is a knowledge which is necessary for us and social life because between human and social are interested to be learnt in depth understanding. Stephanie Meyer is known by people throughout the world only after the success of her Twilight saga. A lot of people not only in literature field but also another field around the world know her as a talented author. Stephanie Meyer was born on December 24, 1973 in Harford, Connecticut, and got the growth in Phoenix, Arizona. Since childhood Meyer has a great interest for reading and really found of some classic authors such as: Jane Austen, Charlotte Bronte, and Margaret Mitchell. Meyer got its high school in Scottsdale, Arizona. In this place, Meyer was awarded by a National Merit Scholarship that was used to join Brenham young University, in Provo, Utah, and taking a major of English Literature. In 1994, Meyer was married, and has three sons, Gabe, Seth and Eli. Six years later, Stephanie Meyer without any purpose showed the ability in writing, and then can be an author. Meyer’s success career began with the idea for Twilight came from the dream on 2003. The dream was about a human girl and vampire having special relationship in love, but unfortunately the vampire needs for the girl’s blood. Based on this dream, Meyer writes the text. Meyer had transformed the dream into a completed novel about three months, thought Meyer never intended to publish Twilight and was writing for her own enjoyment. Because of the sister’s enthusiastic response toward the text, Meyer didn’t pass the way in essay way, because of getting many rejections, until finally got good response from Jody Reamer of writer House.(http://en.wikipedia.org/wiki/Stephanie_Meyer ) A short part of the author’s personal life above, arrows the attention finally choosing Stephanie Meyer as the object in this study. It personally gives a great interest and being a fan of the author because of her writing career background in literary work was not similar to other authors in common. Commonly many authors wrote novels based on the personal life and exploring deeper from its sources. In contradictory, Meyer wrote the novel based on its own inspiration and imagination which was not in purpose at all. Another important reasons to interest to this author is because of the great succeed after publishing the first novel Twilight in 2005 with a print run of 7500 copies. It was sold to over 26 countries and translated into 20 languages. The story featured Bella, a high school girl in rural Washington state fallen in love into dangerous romance with Edward Cullen who was a vampire. Then, although Twilight story come from the imagination or only a fiction novel, it is really interesting to follow. The romance and the different life and world between human and vampire here is able to present the main characterization in a unique way. It is only the personal statement, but also the fact that brought many awards and honors to this novel, such as New York Times Editor’s Choice, One of Publisher Weekly’s Bets Children’s Book of 2005, Publisher Weekly “Best Book of the Year”. One of the American Literary Association’s Top Ten Best Books For Young Adult and Top Ten Books For Reluctant Readers, One of School Library Journal’s Best Book of 2005, Amazon.com’s Best Book of the Decade. These awards and honor are enough to show and capability of Stephanie Meyer as the author (http://en.wikipedia.org/wiki/Stephanie_Meyer). New moon is the series novel in the Twilight Saga. This novel is popular because of it has been produced in a movie theater on November 2009. New moon is published on September, 6th 2006. The book was originally released in hardcover on September 6, 2006 with an initial print run of 100,000 copies. Upon its publication in the United States, New Moon was highly successful and moved quickly to the top of bestseller lists, becoming one of the most anticipated books of the year. It peaked at #1 on both the New York Times Best Seller list and USA Today's Top 150 Bestsellers, and was the biggest selling children's paperback of 2008 with over 5.3 million copies sold. Moreover, New Moon was the best-selling book of 2009 and has been translated into 38 languages. A film adaptation of the book was released on November20,2009.(http://en.wikipedia.org/wiki/New_Moon_%28novel%29)This novel tells about the anxiety of Bella. She gets a lot of conflicts with her love story with Edward. First, when she celebrates her birthday. She is 18 but Edward was 17 years old. Edward will not become 18 years old forever. Because of his growth kinetics stops when he becomes a vampire. Everyone will know that Bella is older one year than Edward. Bella dreams about her meeting with her grandmother. But it is not her grandmother, but it is her with Edward beside her and Edward stays 17 years old. Bella’s anxiety is caused by Edward leaves her alone. This is caused by Bella’s birthday party in Edward’s house. In Edward’s house there are 7 vampires. They are Carlisle Cullen as Edward’s foster father and his wife Esme Cullen, Edward’s brothers are Emmett Cullen and Jasper Cullen, and also his sisters named Rosalie and Alice. Emmett is Rosalie’s boyfriend and Jasper is Alice’s boyfriend. There is an accident that makes Bella produces so many bloods from her arm. When Bella opens the present from Esme, intuitively her hand is scratched by ribbon. Jasper as a new vegetarian vampire smells Bella’s blood and hunts her but Edward pushes Bella until she drops and crushes the table and it makes Bella produces more blood than before. Edward moves to another country because he wants Bella always safe without many vampires around her. So, he decides to leave Bella alone. Edward says that he moves to another country because all the people know that Carlisle look younger than his age. But Edward has one asked; he wants Bella never doing the stupid mistake. Since Edward leave her alone, Bella abstracts in her room every day. She just writes an email day to day to Alice until more than 10 emails but not one email has replied by Alice. It is interesting to study further about Bella’s anxiety and how she has the responses to the anxiety. RESEARCH METHOD This thesis is regarded as a descriptive-qualitative study and use a library research. Therefore, the data will not be in number. The descriptive method of his study can be elaborated as follows The main source of the study is taken from New moon. New moon is the second of the Twilight series. A novel by Stephanie Meyer published in New York at 2005-2008 and using English language. The genres of this novel are romance, fantasy, young-adults and fiction. .The data of this study are in the form of the quotations, phrases, dialogues or monologues that represent the speech, thought, actions and attitude of the main character in relation to her anxiety. This study of anxiety will apply the theory of self defense mechanism by Sigmund Freud to depict Bella’s anxiety. Hilgrad is also support in this case about the meaning of anxiety and the other concept is from Freud. Freud conceptualized three types of anxiety which are neurotic anxiety, moral anxiety, and reality anxiety and also there are symptoms of anxiety, those are generalized anxiety disorder, panic disorder and stress disorder. The causes of anxiety is also including in this proposal to support the concept of anxiety. The first step off doing analysis is sufficiently accomplished by reading the novel. After being agreed that this novel is incredible to use then makes some titles based on the novel. Next step is making an outline for this study. The next step is collecting the data; it contains the quotations based on the statements of the problems. Then next step is classifying the quotations based on the statement of the problems of the analysis. There are two statements of problems, the first is depiction of the main character’s anxiety in Twilight and the second is the response of the main character against the anxiety in Twilight. Each problem will be analyzed by using in line with the statement of the problems. Then, conclusion will be drawn from the whole analysis. ANALYSIS This chapter is divided into two sections based on the statements of the problem. The first analyze how is Bella’s anxiety is depicted by apply the theory of anxiety. Second is to analyze how the responses her anxiety feeling using the theory of defense mechanism. Depiction of Bella’s Anxiety The depiction of Bella’s anxiety will show how Bella experiences her anxiety throughout the novel. In this sense her anxiety can be presented through the description and symptoms her anxiety. Each will be discussed as follows. Description of Bella’s Anxiety Bella is a woman who has boy friend named Edward Cullen, but he is a vampire while Bella is a human being. When her age is seventeen years old, she moves to Forks and she meets with Edward is known as a vampire. “My room hadn't really changed all that much in the seventeen years since my mother had been here. The walls were still light blue, the same yellowed lace curtains hung in front of the window. There was a bed, rather than a crib, but she would recognize the quilt draped untidily over the top.” (Meyer: 32). Bella has problem with her family. Before she moves to forks, she lived with her mother in Phoenix. Forks and phoenix have different season. Phoenix is the hottest place, but Forks is the wettest place. “The kind of blinding clear sun that never shone on my drizzly new hometown in Forks, Washington.” (Meyer, 3) Their parents had divorced when Bella was a child. Her mother took her away from her father because her father’s job is just a police in a small city. She thinks that the salary as a police in the small city is not enough to fulfill the daily needs. Actually, she does not love to live in forks because she does not like with rain. Forks is a place where the famous city which has the highest volume of rain. But, Bella loves forks and wants to stay in forks because of Edward. If I could be sure of the future I wanted, sure that I would get to spend forever with Edward, and Alice and the rest of the Cullens (preferably not as a wrinkled little old lady)… then a year or two one direction or the other wouldn't matter to me so much. But Edward was dead set against any future that changed me. Any future that made me like him—that made me immortal, too. (Meyer: 7) She does not care about what her hate is. Bella really loves to Edward. She wants become a vampire like Edward, because if she becomes a vampire, they can life together without a danger. The danger is because their food is blood of human. Someday, one of them can kill her because Bella is a human being if Bella is always around them. She wants that in the future, she will become a vampire like Edward because it makes them to live together and also there will no danger. The willing of Bella to become a vampire is dishonored by Edward because he thinks that to be a vampire is not good choice for her. The willing itself is Edward changes her become a vampire. But, Edward promises to Bella that he will change her become a vampire when the end of the school year. “Maybe he wouldn't want to wait till the end of the school year, maybe it would have to be now.” (Meyer: 32). Vampires are immortal. They cannot die even they must drink a litter of poison. "You humans have it so easy! All you have to do is throwing down one tiny vial of plant extracts…" (Meyer: 11). It means that vampires cannot die easily like human. Because of that, Edward does not want Bella becomes a vampire, because he thinks that vampire is deprecation from God. It can be seen in this quotation bellow: "I'm sure all this sounds a little bizarre, coming from a vampire." He grinned, knowing how their casual use of that word never failed to shock me. "But I'm hoping that there is still a point to this life, even for us. It's a long shot, I'll admit," he continued in an offhand voice. "By all accounts, we're damned regardless. But I hope, maybe foolishly, that we'll get some measure of credit for trying."(Meyer: 20) Edward’s statement makes Bella so sad. She does not want Edward will die because of her. Bella does not want that Edward will leave her alone. She cannot live without Edward even Edward is a vampire, but his successes take the Bella’s attention and more over Bella’s love. Bella really wants to be a vampire even Edward’s father tells to her about the lacks of vampire. She does not care about what he say is. The dream is to live with Edward forever. She never thinks what will happen if she become a vampire because it is her choice. "It's my choice," I insisted. (Meyer: 21). That condition makes Bella fell depress because she will go older step by step than Edward every year if she still be a human being. Bella has been doing anything to make change Edward’s mind toward Bella’s life. Anxiety is the condition when somebody afraid, fear, and worried about something. It caused by a situation that treated well-being of organism and the threats of physical harm, threat to self esteem or the pressures to perform beyond individual capabilities. The anxiety is caused by internal conflict and is skin to fear. This condition becomes important study because it reveals about how anxiety gives important role to choose and identify who it is. This situation happens to the main character in New Moon Bella. Bella is the main character of this novel. First, she suddenly feels afraid when she must faces about her age. Bella is a human being who loves a guy named Edward but her boyfriend is a vampire. In this novel tells that a vampire will never increase her or his age. So, Bella panics about this condition. She dreams meet with her grandmother, even though her grandmother was dead six years ago. Bella knows that it is not her grandmother, but herself in the future with Edward who is standing beside of her. Her dream tells what will happen in the future if she still becomes a human. So, it makes Bella confused and panic if that dream will really happened to her. The second is when Edward leaves him alone because he believes if Bella is beside him, she will get a dangerous situation. Edward’s families are vampires who suck blood of human. So, that is the reason why Edward leaves Bella alone, because he wants to save Bella from the attack of his families. That situation makes Bella so sad, she feels alone when Edward leaves her, and she keeps herself in her room day to day moreover for months. He threw himself at me, flinging me back across the table. It fell, as I did, scattering the cake and the presents, the flowers and the plates. I landed in the mess of shattered crystal. Jasper slammed into Edward, and the sound was like the crash of boulders in a rock slide. There was another noise, a grisly snarling that seemed to be coming from deep in Jasper's chest. Jasper. (Meyer:16) Bella experiences the anxiety. The first is reality anxiety. Reality anxiety is the condition in the real and it makes somebody gets anxiety. For example, Romeo and Juliet are the couple who love each other. The reality is their families do not agree with their relationship. Romeo’s parents are the enemy of Juliet’s parents. When they know about the relationship between both of them, their parents reject each other. They met covertly behind their parents. Until they feel afraid about their relationship. So, they decided to finish their life even though in the first is just Romeo’s planning, but finally Juliet decides to drink that poison too. Bella feels so painful with the reality. She loves Edward who is a vampire. Actually, she does not care about who Edward is. She just cares about the increasing her age. She afraid if Edward do not accept the willing of Bella is to change her becomes a vampire as him, she will increase her age and more over, she will be older than Edward physically. “Every day I got older, but this was different, worse, quantifiable. I was eighteen. And Edward never would be.”(Meyer: 5) Bella says to herself that the reality is never changing. She and Edward have different life. Bella is a human being while Edward is a vampire. She must accept it that she is older one year than Edward because basically all the people who live in forks know that Edward’s age is seventeen years old. Bella knows that she is older than Edward and that condition will continue forever. Edward never will be eighteen years old because when he was seventeen years old, Carlisle sucked him blood and he changed become a vampire, and now he is still seventeen years old. So, his growths stop when he becomes a vampire. At that time, there is an epidemic that makes his family must die but he is helped by Carlisle. Carlisle had changed Edward become a vampire because Edward’s mother wanted Edward to stay in this world or the other option is he must still alive in this world. Carlisle hadn’t choice, immediately he changed Edward same as himself, it is a vampire. “Edward and Alice weren't really related (in Forks the story was that all the Cullen siblings were adopted by Dr. Carlisle Culler and his wife, Esme, both plainly too young to have teenage children), but their skin was precisely the same pale shade, their eyes had the same strange golden tint, with the same deep, bruise-like shadows beneath them. Her face, like his, was also startlingly beautiful. To someone in the know—someone like me—these similarities marked them for what they were.”(Meyer: 5) This statement explains the differences between Edward and Bella. Edward’s skin is precisely the same pale shade; his eyes had the same strange golden tint, with the same deep, bruise-like shadows beneath them. His face is also startlingly beautiful. Those are the characteristics of vampire. Physically, they are similar to humans being, but technically they are different from them. Human being will not have the characteristic like Edward’s characteristic. Vampire physically is like a human being; they can walking, working, school, talking with other, writing, thinking about something, carrying, running, and also they have felling like Edward’s feeling to Bella, and even they can eating something, only one kind food that they eat, it is blood. But, they cannot breathe and their heart stop beat when they become vampire. This condition is different from Bella’s characteristic. As cited bellow: “When I went to brush my teeth, I was almost surprised that the face in the mirror hadn't changed. I stared at myself, looking for some sign of impending wrinkles in my ivory skin. The only creases were the ones on my forehead, though, and I knew that if I could manage to relax, they would disappear. I couldn't. My eyebrows stayed lodged in a worried line over my anxious brown eyes.”(Meyer: 5) Human being needs to wash their body because to remove the duster from their body. They also need to brush their teeth because when they are not brush their teeth, their gasp will so unpleasant odor, it is caused there are so many germs in their mouth are not brushed. While, vampires do not need to brush their teeth because they do not breath. So, their smell will be nice. Vampires will not feel afraid about their ages; it is different from Bella or the other humans being. Bella looks herself through a mirror. Human being willed become old with one characteristic is wrinkled in their face. While, vampires will not become older because their growths have stopped when they become vampire. “She's very pretty. He made a disgusted sound. "I don't envy him the girl—just the ease of the suicide," he clarified in a teasing tone. "You humans have it so easy! All you have to do is throw down one tiny vial of plant extracts… It's something I had to think about once, and I knew from Carlisle's experience that it wouldn't be simple. I'm not even sure how many ways Carlisle tried to kill himself in the beginning… after he realized what he'd become…" His voice, which had grown serious, turned light again. "And he's clearly still in excellent health.”(Meyer: 11) This is Edward’s statement when they are watching a film entitles Romeo and Juliet. He tells about the death. A human is easy to death but vampires are not easy to finish their life. A human just drink a poison so he or she will die. It is the one of characteristic of vampire, they cannot die easily. Romeo and Juliet is popular story. All the people in the world know about this story. The ironic ending which is Romeo dead because he knows that Juliet is dead, so he decides to finish his life too because he cannot life without Juliet. It is caused by their parents are hostile each other. Romeo and Juliet have different social background. Romeo is a poor man while Juliet is a rich woman. Their relationship is unaccepted by their parents. Juliet has an idea to feign to die because she wants their parents and all the people know that he has death, so he cans life with Romeo forever. But, ironically Romeo does not know the planning of it. She feels sadness when she knows that Romeo was dead, so she decides to finish her life too. "You humans have it so easy! All you have to do is throwing down one tiny vial of plant extracts…" (Meyer: 11). This statement is when Bella and Edward are talking about the story of Romeo and Juliet who love each other but must die in the last story because of a bottle of poison. Edward has been watching this story in many times so he knows everything about this story. Edward talks to Bella when she has been bitten by James who is non-vegetarian vampire but now, he is dead because of the attack of Edward’s family. James wants to bit Bella because Bella’s blood is very interesting him. James success bit Bella but Edward save her. At that time, Edward fells despondent to that condition. He feels afraid if Bella cannot be saved by him. Edward will die too, but it is not easy for vampires. They will not die if only drink a bottle of poison or more over a thousand litter of poison. It makes Bella afraid and fear about it. She won’t Edward die because of her or the other option is she won’t Edward goes away from her. But the reality, Edward will not change Bella becomes vampire like him. Like Carlisle, he tries to suicide but until now, he is still life with the health condition. “This bleak date had lurked in ambush, waiting to spring.”(Meyer: 5). She sees that her birthday like a monster is hiding but someday will kill her suddenly. The reality with the frightened about the increase her age makes Bella more panic. So that, she says that her birthday is Blake date. “I'd been dreading this day for months.” (Meyer: 5). Even though, she feels afraid with her birthday, but finally that day come occasionally. She has afraid with her birthday for months. Generally, if somebody increases her or his age, she or he will happy and they will celebrate it with their friends or someone that they loved. And even they will happy if someone gives her or him a present. But, Bella is different from them. She does not like if her birthday will be celebrated by Edward’s family, especially they give her some presents. When Bella opens a present, his finger is sliced by paper. Bella gives out just a little blood of her finger; nevertheless jasper who is a new vegetarian vampire feels so hungry with Bella’s blood and immediately pounces on Bella. But Edward prevents him. Edward push Bella until she crashes a piano and it makes Bella gives out more blood from her arm. All the vampires in that room fell hungry and look Bella hungrily, just one is not, and he is Carlisle. Carlisle is Edward’s father. He is a doctor. He has not fell hungry with human blood because he has been familiar to human blood. He has lived in this world for many years. Bella’s blood drops fast and makes arm’s Bella is hurt. This is the real condition if she closes vampires because their favorite food is human blood. This statement is explained in bellow: “"Shoot," I muttered when the paper sliced my finger; I pulled it out to examine the damage. A single drop of blood oozed from the tiny cut. It all happened very quickly then. Edward threw himself at me, flinging me back across the table. It fell, as I did, scattering the cake and the presents, the flowers and the plates. I landed in the mess of shattered crystal. Jasper slammed into Edward, and the sound was like the crash of boulders in a rock slide.”(Meyer: 16) It makes Edward think hard about it. He decides to leave Bella alone. The purpose of Edward’s planning is to save the life of Bella. If Edward and his family go away from Bella, Bella will be safer because there is no vampire around her. There is no the accidents like in Edward’s house last night. That event makes Bella fells anxious because she really loves him so much. Bella does not want that Edward will leave her alone. She thinks that Edward will follow her but in fact Edward leaves her alone. His answer confused me. I thought the point of leaving was to let his family live in peace. Why did we have to leave if they were going? I stared at him, trying to understand what he meant. (Meyer: 37) The second anxiety is neurotic anxiety. It is caused by the events that make someone think about everything that make her or him anxious. For example, when a student stoles her mother’s ring. She fells afraid if her mother or some people know her sin. She thinks if somebody knows it, her mother will be mad to her and she will get the punishment. Bella’s neurotic anxiety is when her age increase one year. She thinks that she is older one year than Edward because of her dream. She afraid her dream will come true. She does not want become old like her dream. She dreams that she meets her grandmother. In fact, her grandmother was dead six years ago. “I was ninety-nine point nine percent sure I was dreaming.”(Meyer: 3) This statement explains that Bella is a human being who is dreaming and a dream itself is one of the characters of Bella. Bella is really sure that she is dreaming. This is the first sentence in the novel New Moon that explains how Bella’s character is. This statement states that Bella afraid with something that will happen in the future. This is one of Bella’s characteristics. She will dream if she afraid with something bad that will occurs to her. “The reasons I was so certain were that, first, I was standing in a bright shaft of sunlight—the kind of blinding clear sun that never shone on my drizzly new hometown in Forks, Washington—and second, I was looking at my Grandma Marie. Gran had been dead for six years now, so that was solid evidence toward the dream theory.”(Meyer: 3) That quotation tells that she is really dreaming about the condition of forks. The city of Forks is the wettest city in the world. She dreams that she is standing in a bright shaft of sunlight, but in the next sentences tell that it will not happened in Forks, Washington. This is the comparison between the true condition and Bella’s dream. Firstly, Bella lives with her mother in phoenix. Phoenix is the hottest city. The sun shine is always shines phoenix. She must move to forks with her father. Her mother and her father have divorced. Her mother asks Bella out from her father’s house when Bella 7 years old. But when her mother married again with another guy, she decides to move in forks to life with her grandmother because her step father is an athlete who always moves from one city to another city for following the competition. In there, Bella meets Edward. Bella falls in love to Edward. Moreover, she dreams meet Edward in her dream. The second is she dreams about her grandmother. She was dead six years ago. Actually, Bella does not sure that she is her grandmother. Bella sure when she knows the characteristics of someone who is standing in front of her. So, it is the true explanations to tell that Bella is dreaming. “What was he doing? The whole reason he lived in Forks, the rainiest place in the world, was so that he could be outside in the daytime without exposing his family's secret.”(Meyer: 4) Sunny day will never occurs in forks, so that statement is more explaining about the dream of Bella. That is a reason why Edward different from other. He can go outside in the day time because the sun shine will not shines forks, so he will not expose his family’s secret. The secret is they are vampire. If there is somebody knows that secret, they will die. “Well, Gran, you might have noticed that my boyfriend glitters. It's just something he does in the sun. Don’t worry about it.”(Meyer: 4) It is the statement of Bella to her grandmother when Edward suddenly comes around them. “Glitters” mean that Edward’s skin will shine when he does in the sun. In this novel tells that if a vampire goes outside in the day time, her or his body will gives out the shine like a diamond, so beauty and different from other. If they get it, all the people will know who they are. Vampires must keep their secret if they do not want to die. That is the reason why Edward and her family live in forks and also the reason about the dream of Bella. Bella feels afraid to that situation. She nervous because of Edward’s skin is glitters when the sun shine is shining his body. She thinks that her grandmother will know who Edward is. She feels afraid, if Edward will die because her grandmother or human being knows the secret of Edward. Bella is really loves Edward, so she does not want Edward will die. Bella wants to keep the Edward’s secret even though from her family. But, Edward suddenly comes around them. It makes Bella panic to that situation. She said to herself that everything is all right. But it is just to calm Bella down. There are so many thinks about the anxious in Bella’s mind, such as her grandmother will know the secret of Edward and the more dangerous is Edward will die if there is somebody knows about his secret. “Gran hadn't changed much; her face looked just the same as I remembered it. The skin was soft and withered, bent into a thousand tiny creases that clung gently to the bone underneath. Like a dried apricot, but with a puff of thick white hair standing out in a cloud around it.” (Meyer: 3) That statement draws about characteristics of an old woman. They are The skin was soft and withered, bent into a thousand tiny creases, it means that she is really old because not only one crease but also a thousand tiny creases. The next statement is clearer about white hair standing out in a cloud around it. If someone has white hair, it means that really old. Actually, it is not about her grandmother. But it is just the picture of somebody who is similar to Bella but they have different age. Grandmother is the picture of a women that so old. She dreams about her grandmother who has a thousand puckers in her face. She looks her grandmother still like six years ago before her dead. There is not much change. “Our mouths—hers a wizened picker—spread into the same surprised half-smile at just the same time. Apparently, she hadn't been expecting to see me, either.”(Meyer: 3) The word of wizened picker is a form that clarifies about a human being who is looked by Bella which is really old because she has wizened picker. It is just happened in the mature in ages. Their bone will brittle, their hair will change from black hair to white hair, their eyes will lose the accommodation to see something, their teeth will fall one by one, and also they will lose their memorizes about something. There is the word “at the same time” means that they do it in the same time. It is not intuitively, there are some events that they do in the same time, when a man calls Bella. She thinks that there is the oddity with her grandmother because they always do anything in the same time. Bella starts fear to this condition. “It wasn't Gran who called my name, and we both turned to see the addition to our small reunion. I shot a panicked glance back at Gran, and saw that it was too late. She was just turning to stare back at me, her eyes as alarmed as mine. Gran's expression surprised me. Instead of looking horrified, she was staring at me sheepishly, as if waiting for a scolding. And she was standing in such a strange position—one arm held awkwardly away from her body, stretched out and then curled around the air. Like she had her arm around someone I couldn’t see, someone ivisible…” (Meyer: 4) That statement explains more about the event that occurs in the same time. Everything that Bella does, her grandmother will do it too, if Bella turn right to see that somebody join in their small reunion, her grandmother will do it too. The second, if Bella looks her grandmother sheepishly, she will do it too again. It makes Bella becomes confused with this situation. She confuse about the behavior of her grandmother does. Bella becomes speech less with it. She starts to look for what the fact about this situation. She looks her grandmother carefully. But, her grandmother does it too. It shows in the quotation bellow: “She mimicked the movement exactly, mirrored it. But where our fingers ,should have met, there was nothing but cold glass…”(Meyer: 4) She starts conscious that it is not grandmother but it is herself. She is looking herself by a mirror. In her dream, she looks an old women as she knows that she is her grandmother who was dead six year ago. When she touches that mirror, she conscious that it is the picture of her in the future. Actually, it is not about her grandmother. But it is just the picture of somebody who is similar to Bella but they have different age. Grandmother is the picture of a women that so old. The shadows of her dream come over to her life and it influences to her life. It is visualized by her felling to Edward. She wants becomes vampire like Edward but Edward does not want it. If Edward will not change Bella becomes vampire, her dreams comes true. Anxiety is such painful state that Edward has been leaving Bella alone. The time when she starts know about what actually the purpose of her boyfriend leaves her alone. Every time Bella thinks about Edward that makes her anxious. “I was afraid of the time I'd spent unconscious, afraid that he might have been thinking about right and wrong again while he watched me sleep. The anxiety seemed to ratchet up the intensity of the pounding in my head.”(Meyer: 29) “Again, I didn't sleep well. (Meyer: 35).” All the events in the Edward’s house make Bella cannot sleep well. All the night after that event, she always thinks what will Edward does to her. She thinks that Edward is a perfect guy. He always comes to Bella’s house without any calls from Bella. He always accompanies her all the times even Bella is sleeping. The other reason is caused by the absence of Edward. For two days after the accident in Edward’s house, Edward never comes again in Bella’s house. She feels fear about Edward’s mind. She decides to meet and talk seriously with Edward about the accident last time. For two days in school and at home without Edward makes Bella confused because she cannot meet and talk with Edward. She wants clarifying about the accident. If she does not meet with Edward, she thinks that she cannot clarify it with him. I didn't answer. I couldn't think of a way to protest, but I instantly knew that I wanted to. I didn't like this. This is bad, this is very bad, the voice in my head repeated again and again. (Meyer: 36) This statement states when Edward invites Bella in a jungle near with her house. She knows that it is not good for her because Edward will not invite her to enter the jungle. The jungle is a place where is very silent, dark, and also so cold because there are so many trees inside of it. She always thinks that the worst will be happened to her. But she has not a decision because actually Bella wants it too. She does not afraid with the condition inside of the jungle, she just afraid with what will Edward says to her because it is more important than the darkness of the jungle. She thinks that Edward will say the bad news to her about the accident in the Edward’s house. “It was what I wanted, I reminded myself. The chance to talk it all through. So why was the panic choking me?”(Meyer: 36). She feels really panic with that time. She makes sure herself that everything will be alright. She thinks that Edward will give her a good solution which is to change Bella becomes a vampire and live with him forever. In this session, Edward will leave Bella alone without Edward. he will go away from forks. He tells to Bella that all the people in forks will know his secret, but it is just the reason to make Bella sure about what Edward’s explanation. It makes Bella speak angrily to him. She thinks that Edward will take her out from forks and live with him. Actually, Edward does not want it. He decides to leave Bella alone in forks. The true reason is to save Bella’s life because if there are vampires around her, her life will always be danger if take a look at the food of vampires. The accident in Edward’s house last night makes Edward thinks hard about this option. He loves Bella but he does not want to make her always on danger condition. So, he decides to go away from bell’s life. But, it is not good for Bella because she really loves to Edward. "No! This is about my soul, isn't it?" I shouted, furious, the words exploding out of me—somehow it still sounded like a plea. "Carlisle told me about that, and I don't care, Edward. I don't care! You can have my soul. I don't want it without you—it's yours already!" (Meyer, 37) Bella really loves Edward until she does not think about how important her soul is. She has lost her common sense. She thinks that her soul is not important for herself because she thinks that her soul is always staying beside Edward. If Edward decides to leave her alone, it means that she will lose her soul. She needs Edward to make her stay alive and accompany her in every moment. Actually, Bella is a serious woman about love. There are so many boys love her but she just love Edward even he is a vampire who drinks blood of a human. Human being will afraid if they meet with something that really dangerous. Vampires are dangerous for humans being because they suck blood of human being. They have big willing to suck blood of humans. If vampires meet with humans, they will bite and suck their blood until they lost her life or death. Generally, all the people in the world afraid with the death, but Bella do not afraid with it. It is caused by her willing about Edward’s love and his absence. When she knows that Edward is a vampire, she does not afraid because her love is bigger than her afraid against the danger that will be happened in the future. She believes that Edward will save her and he promises to her that he will not leave her alone or he will change Bella becomes a vampire in the best time. But, Edward does not fulfill his promise to her. Bella feels so disappointed to Edward. Her disappointed against Edward makes her depress and stressful. "Of course, I'll always love you… in a way. But what happened the other night made me realize that it's time for a change. Because I'm… tired of pretending to be something I'm not, Bella. I am not human." He looked back, and the icy planes of his perfect face were not human. "I've let this go on much too long, and I'm sorry for that."(Meyer: 38) That is the true reason from Edward that why he must go away from Bella. He hopes Bella will save and always in endanger situation if there will no vampires around her without exception of him. He is a vampire even that he really loves to Bella but he must go away. The accident in the Edward’s house makes Edward conscious that he and his family will make Bella in danger situation. He told to Bella in a bad situation in a jungle near from Bella’s house that he is not a human. Actually, he wants to live with Bella but the reality makes Edward must go away from her. He apologizes to Bella because he cannot keep his promise to Bella that he will change Bella to be a vampire after Bella finishes her school. He feels so tired because he has pretended like a human generally. Edward has been pretended like a human more than 100 year. For that time, he never dated with the other girl, it is just with Bella. When he meets her at the first sight, he felt that there was something different in Bella from the other girl. Edward has sixth sense, it is he can read what a human think is, but Edward cannot read Bella’s mind. After that, he loves Bella and always keeps Bella in every danger. But now, he will leave her alone, it will make Bella more depress because of her love. Edward is a boy that make Bella believe in love, she trust in Edward even they have different life. The difference between both make they must keep the distance when they will kiss each other because Edward has sharp tooth and they will make Bella’s lip produces so many blood if they do not keep it. The bite of a vampire will give a poison which is really danger if there is a person gets it. If a person gets it, they will change become a vampire more over if the desire of vampire is bigger to suck his or her blood, that person will die. Bella has big desire to kiss Edward, but Edward always keep the distance because he won’t Bella will die or change to be a vampire in a bad time. That is one of the reasons to leave Bella because he will not kill her. He has bored because he cannot give what Bella’s desire is. Symptoms of Bella’s Anxiety There are so many problems that people must faces them. They show the symptoms of anxiety. Basically, there are three symptoms of anxiety, they are GAD, Panic disorderand Stress disorder. As cited bellow: Generalized Anxiety Disorder GAD is a mental health condition in which a person is often worried or anxious about many things and finds it hard to control this anxiety. If someone feels anxious, she will gets all the symptoms that she shows to all the people and herself. That is caused by feeling fear and afraid towards unpleasant moment. For example is afraid because they did the mistakes and they won’t that others will know it. And also, there is a student feels disappointed because his scores are bad and he cannot continue his school in the next grade. There are three kinds of the symptoms of anxiety. They are GAD (Generalized Anxiety Disorder), Panic disorder and Stress disorder. Generalized anxiety disorder is a relatively common anxiety problem, affecting 3-4% of the population that turns daily life into a state of worry, anxiety, and fear. As with many mental health conditions, what causes generalized anxiety disorder isn't fully understood. It may involve naturally occurring brain chemicals (neurotransmitters), such as serotonin, dopamine and nor epinephrine. It's likely that the condition has several causes that may include genetics, your life experiences and stress. Bella gets these symptoms when her love named Edward goes away from her. She feels there’s no way out of the vicious cycle of anxiety and worry, and then becomes depressed about life and the state of anxiety they find themselves in. generalized anxiety usually does not cause people to avoid situations, and there isn’t an element of a “panic attack” involved in the prognosis either. At other times, thoughts seem almost non-existent because the anxious feelings are so dominant. Feelings of worry, dread, lack of energy, and loss of interest in life are common. Restlessness is one of the most common symptoms of anxiety. It's the feeling of being unable to sit still, or feeling as though you're on edge and something is about to or needs to happen. There are a lot of symptoms of anxiety that are complex, caused by issues that are difficult to explain. Restlessness is not one of those symptoms. The cause of restlessness is very clear: a constant surge of adrenaline as a response to the fight or flight system. Adrenaline is nature's energy. If you were in the wild and running away from a predator, it doesn't matter how tired you are – need to have as much energy as possible to make sure you get out of there safely. Adrenaline provides that energy. "Don't." My voice was just a whisper now; awareness was beginning to seep through me, trickling like acid through my veins. "Don't do this."(Meyer:38). Bella screams because she does not want that Edward will go away from her. She rejects what Edward’s desire to leave her clearly. She is really suppressed by this situation. She cannot do anything to make Edward just stay with her. She does not know how to make sure Edward that she needs him and cannot live without him, she just screams to give a sign that she rejects it. “Acid” means that really wrinkled. If it mixes with blood, it will so hurt. That is just an expression to tell Bella’s mind. “My whole body went numb. I couldn't feel anything below the neck.”(Meyer: 38). Not only she feels so hurt but also makes her speechless. She is really shocked with it. She never suspects that Edward will leave her. “She couldn’t feel anything” means that her mind is full of anxiety because Edward speaks seriously that he will leave her. My knees must have started to shake, because the trees were suddenly wobbling. I could hear the blood pounding faster than normal behind my ears. His voice sounded farther away. He smiled gently. "Don't worry. You're human—your memory is no more than a sieve.”(Meyer: 39) It draws the condition of Bella at that time. She is really shocked. Her knees cannot move, and she hears the blood pounding faster than normal her ears. Knees are part or the human’s body. Knee is the most complicated and largest joint in our body. It’s also the most vulnerable because it bears enormous weight and pressure loads while providing flexible movement. She cannot concentrate and it makes her feels so cold. even thought, she is already in the forks or be familiar with the temperature in forks, she never feel so cold in her body because she wears coat, gloves that makes her always feels hotter. Generally, human being will show feel it when they are sick, and stay in the low temperature such as mountains. And also, there are some people will feel it when they are in danger situation. For example is when a police asks to the criminal about his crime, the criminal will not be honest first because he afraid if the police will put him in a jail. At that time, the criminal will not concentrate to the questions of the police because he fells afraid. I was dizzy; it was hard to concentrate. His words swirled around in my head, and I heard the doctor at the hospital in Phoenix, last spring, as he showed me the X-rays. You can see it's a clean break, his finger traced along the picture of my severed bone. That's good. It will heal more easily, more quickly. ( Meyer:39 ) It is the same situation as Bella. Bella in a danger situation because she thinks that Edward is her soul, if he leaves her, it means that she will lose her soul. She cannot concentrate because she thinks that Edward has gone, thinks about the Edward’s treason so she feels so disappointed, and also she thinks if they are in the same life, they will life forever. Panic Disorder Bella is getting the panic. She starts too conscious that his soul has gone. His soul is Edward. She cannot do anything to follow him because Edward so fast and it is impossible if a human can reach him. With shaky legs, ignoring the fact that my action was useless, I followed him into the forest. The evidence of his path had disappeared instantly. There were no footprints, the leaves were still again, but I walked forward without thinking. I could not do anything else. I had to keep moving. If I stopped looking for him, it was over. (Meyer: 39) Edward runs so fast without evidence in the land and it makes Bella does not know where Edward is. Actually, she wants to follow him but it is impossible even she has tried to enter the forest until the deepest of it but she cannot find him. “It was over” means that the memories and Edward’s footprints have gone. She cannot life with him again. Her life is offer without Edward. I walked and walked. Time made no sense as I pushed slowly through the thick undergrowth. It was hours passing, but also only seconds. Maybe it felt like time had frozen because the forest looked the same no matter how far I went. I started to worry that I was traveling in a circle, a very small circle at that, but I kept going. I stumbled often, and, as it grew darker and darker, I fell often, too. (Meyer: 40) She tries to walk and walk to the deepest of the forest to find him because she feels so panic. She does not care about the darkness of the forest; she does not care about the silences and also the dangers of the wild animals because she does not care about herself again. The panicity will make somebody do the impossible action, like she does because of her mind is full of fear which is bigger than the danger in the forest. She afraid if Edward really leaves her and her night mare will come true. So, she walks to the forest without carrying with herself, she does not think about the dangers that can kill him immediately. She thinks that she is getting lost in the forest. She cannot reach the true way to get Edward. She is just thinking of how to find Edward and explain her feeling to him. When somebody feels anxious because cannot find the answer, he will always in a circle and cannot get out from it. it is same as a burglar who is caught red handed by a police. He will circulate to find the way to out of that place. The Moon is a timekeeper, and the luminary that takes over when the Sun sets.( http://astrology.about.com/od/themoon/a/Introduction-To-The-moon). While, new moon is the phase of the Moon that occurs when it passes between Earth and the Sun, making it either invisible or visible only as a thin crescent at sunset. (http://science.yourdictionary.com/new-moon.) “A new moon. I shivered, though I wasn't cold. It was black for a long time before I heard them calling.” (Meyer: 40). It means that the darkness time because the position of moon is in the middle of sun and earth. So, the shine of sun cannot shining until to the earth because it is closed by moon. It is related to Bella’s condition. It means that she feels lonely because her soul has gone and never back again. In Bella’s mind, Edward is her soul, his sun that shine her life in forks which has no the sun shine. If Edward goes away from her, it means that she has lost the sun shine and she will always in the darkness. I didn't recognize the voice. I thought about answering, but I was dazed, and it took a long time to come to the conclusion that I should answer. By then, the calling had stopped. (Meyer: 40) “She thinks about answering” means that she cannot answer it because she is so tired and feels stuck. She is tired because of she has walked so deep until the deepest of the forest. The calling is from somebody who looks for her. But, when she starts to answer it, the voice has gone. “The rain bothered me a little. It was cold. I unwrapped my arms from around my legs to cover my face.” (Meyer: 40) forks is popular place because it has highest of the rain. Before Edward leaves her, she does not care about the rain but when Edward has gone, she starts feeling so bothered by the rain. She feels uncomfortable with the rain. Stress Disorder Stress Disorder is characterized by the development of severe anxiety, dissociative, and other symptoms that occurs within one month after exposure to an extreme traumatic stress or (e.g., witnessing a death or serious accident). As a response to the traumatic event, the individual develops dissociative symptoms. Individuals with Stress Disorder have a decrease in emotional responsiveness, often finding it difficult or impossible to experience pleasure in previously enjoyable activities, and frequently feel guilty about pursuing usual life tasks. A person with Acute Stress Disorder may experience difficulty concentrating, feel detached from their bodies, experience the world as unreal or dreamlike, or have increasing difficulty recalling specific details of the traumatic event (dissociative amnesia). (http://psychcentral.com/disorders/acute-stress-disorder-symptoms/) TIME PASSES. EVEN WHEN IT SEEMS IMPOSSIBLE. EVEN when each tick of the second hand aches like the pulse of blood behind a bruise. It passes unevenly, in strange lurches and dragging lulls, but pass it does. Even for me. (Meyer:46 ) Bella is getting stress. It is explained by that statement. She feels unconscious that the time has gone. She has slept for months. “Slept” means that doing nothing for months. She just looks out of the window but she does not know what she look is. She has lost her soul, and it makes her so stress. Day by day, she is just waiting for Edward. She hopes that Edward will back again in forks and pick her out. Time is not important for her because she is stress. She thinks that the time is so hurt her in every second hand aches like the pulse of blood behind a bruise. I looked up from my cereal, which I was pondering rather than eating, and stared at Charlie in shock. I hadn't been following the conversation—actually, I hadn't been aware that we were having a conversation—and I wasn't sure what he meant. (Meyer: 46) When somebody is getting stress, she will not concentrate easily or does not have a good serial to do something. She is just playing her cereal without eat it. She does not have a good concentrate or a good desire to eat her cereal. The departure of Edward makes her gets the worst condition. Moreover, it makes her more lose her concentration when somebody is talking to her. She does not know about the theme that they are discussing. When she is just playing her cereal, it is one of the symptoms of stress disorder. She has lost the concentrating and the desire to do something. "I want to know if Edward left you alone out there in the middle of the woods," Charlie insisted. His name sent another wave of torture through me. I shook my head, frantic, desperate to escape the pain. "It was my fault. He left me right here on the trail, in sight of the house… but I tried to follow him." (Meyer: 45) When her father is asking about Edward when he leaves her alone in the forest, suddenly his name is so hurt her. At the beginning of this novel, when Edward calls her name, she is so glad because her love has called her. She always wants to stay with Edward and wasting the time together or if Edward does not come to the school, Bella will look for him immediately. But now, when she hears his name, she will feel hurt and thinks that it is her fault. I always had nightmares now, every night. Not nightmares really, not in the plural, because it was always the same nightmare. You'd think I'd get bored after so many months, grow immune to it. But the dream never failed to horrify me, and only ended when I woke myself with screaming. Charlie didn't come in to see what was wrong anymore, to make sure there was no intruder strangling me or something like that—he was used to it now. (Meyer: 60) She also gets nightmares every night. It is also one of the symptoms of stress disorder. When somebody feels stress, she cannot sleep well. It is caused by a big problem in his thought. Bella is always dreamed about the same nightmares for months. Her nightmares are always makes her wakes up with the screaming. Her father has been familiar with Bella’s condition at night so, he will not come to see what was happened in Bella’s room. Her father has bored to Bella’s condition means that she really gets acute stress disorder. My nightmare probably wouldn't even frighten someone else. Nothing jumped out and screamed, "Boo!"There were no zombies, no ghosts, no psychopaths. There was nothing, really. Only nothing. Just the endles